2016
DOI: 10.1097/htr.0000000000000187
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Evaluation of Traumatic Brain Injury in the United States, 2009–2010

Abstract: Objective Determine the dimensions of traumatic brain injury (TBI) evaluation in U.S. emergency department (EDs) to inform potential application of novel diagnostic tests. Setting United States EDs. Participants National Hospital Ambulatory Medical Care Survey of ED visits in 2009 and 2010 where TBI was evaluated (1) and diagnosed clinically, or (2) with head CT scan. Design Retrospective cross-sectional. Results TBI was evaluated during 4.8 (95% CI: 4.2–5.4) million visits/year; and head CT scan was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
71
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 41 publications
1
71
0
1
Order By: Relevance
“…However, emergency department evaluations for patients with mild TBI have not been sufficiently described [12]. It has been demonstrated that both the standard clinical interview and CT scans have limited sensitivity for diagnosing mild TBI [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, emergency department evaluations for patients with mild TBI have not been sufficiently described [12]. It has been demonstrated that both the standard clinical interview and CT scans have limited sensitivity for diagnosing mild TBI [13].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is likely that a significant fraction of patients evaluated in the emergency department for TBI but did not ultimately receive a diagnosis did in fact sustain TBI. In addition, Korley et al, [12] determined that of the approximately 3.9 million head CT scans obtained in emergency departments each year to evaluate TBI, 91% did not reveal a traumatic intracranial abnormality. The number of negative head CT scans represents high-volume, high-cost, but low-value testing-not to mention increasingly recognized radiation risk [16].…”
Section: Discussionmentioning
confidence: 99%
“…Head computed tomographic (CT) imaging is performed in 3.9 million of these patients, of which 400,000 (10%) are positive for any traumatic abnormality [1]. …”
Section: Introductionmentioning
confidence: 99%
“…In the USA, TBI is evaluated in approximately 4.8 million emergency department visits per year, and 52% of evaluations have involvement with TBI [2]. The incidence of emergency department visits, hospital admissions, and deaths of TBI is 78.2%, 18.5%, and 3.3%, respectively[3].…”
Section: Introductionmentioning
confidence: 99%